ANALISIS PENGARUH CUSTOMER PERCEIVED VALUE, TRUST, DAN SWITCHING COST TERHADAP LOYALITAS PELANGGAN (Studi Kasus Pada Waroeng Spesial Sambal Cabang Tembalang Semarang) - Prabandan, Rahmawati; Sutopo, Sutopo (Faculty of Economics and Business Diponegoro University, 2016)
The purpose of this study is to analize the effect of customer perceived value, trust, and switching cost to the loyalty of customer waroeng SS Tembalang Semarang. The population used in this study is all the people who eatÂ and buy waroeng ss product. The sampling method used in this study was accidental sampling method that is done giving quetionnaires to be filled by waroeng ss customer. This study using multiple regression as statistic tools to test the hypothesis. From the analysis performed in this study, customer perceived value and switching cost has positive significant effect on customer loyalty.